Model Demokratisasi Perusahaan: Studi Kasus di Negara Skandinavia - Sumiyarsih Sumiyarsih (Universitas Mercu Buana Yogyakarta, 2013)
The purpose of this study is to identify models of democratization companies in the Scandinavian countries, what is the purpose and the factors behind its implementation, as well as its association with the industry structure and the labor market. This study found that the model commonly used in Scandinavian countries in implementing democratization is a pattern company stock to employees, which can be done through the provision, purchase, option, ESOP, and SARs. The purpose of the democratization of the company in the Scandinavian countries is recruitment and retention, increase cash flow, Motivation and Performance, Cultural Development Group, Providing for the stock market founders, and the anticipation of expropriation Tool